Photochemical synthesis and optical properties of silver nanodecahedra - Xie, Zhili. (2012)
We report the simulation of silver nanodecahedra using a discrete dipole approximation method. This approach has never before been done on the decahedron shape due to the difficulty in generating the target geometry. The accuracy of the simulation method is verified against the Mie theory method. A positive linear relationship between the edge lengths of silver nanodecahedra and the respective LSPR extinction peaks is proposed. The simulation method‟s potential application in the study of electric field near silver nanoparticles is also explored. The results agree with results simulated from finite-difference time-domain simulations. We also conducted experiment to synthesize silver nanodecahedra using the photochemical method and proposed a simple setup to evaluate the experimental results.